The profile of students' mathematical representation competence, self-confidence, and habits of mind through problem-based learning models - Ahmad Ahmad; Lukmanul Akhsani; Zulkifley Mohamed (IKIP Siliwangi and I-MES, 2023)
Mathematics is an essential subject for students. Teachers, therefore, need to provide innovative learning that develops students' mathematical skills. This study was conducted to determine the effect of a problem-based learning (PBL) model on students' mathematical representation competencies, self-confidence, and habits of mind. It used a quantitative methodology and was conducted on eighth-grade students divided into an experimental class with a PBL model and a control class with a direct learning model. The results showed that the mathematical representation competencies of the students in the experimental class were better than those in the control class. Students' self-confidence and habits of mind also influenced their mathematical representation competencies. It shows that the PBL model positively affects students' mathematical representation competency, self-confidence, and habits of mind. Teachers can use the PBL model to develop their students' mathematical representation competencies by paying attention to students' self-confidence and habits of mind.